Surveying immigrant communities : policy imperatives and technical challenges - DaVanzo, Julie S.; Hawes-Dawson, Jennifer, 1951-; Valdez, Robert Otto Burciaga, 1956-; Vernez, Georges; Andrews, Christina A.; Levitan, Barbara A., 1958-; Peterson, Joyce E., 1934-; Schoeni, Robert F.; Ford Foundation; Rand Corporation; Program for Research on Immigration Policy (U.S.) (Santa Monica, CA : RAND, 1994)
To assess the feasibility of a large-scale survey of immigrants, the authors conducted a pilot study, the Los Angeles Community Survey of Salvadorans and Filipinos, in 1991. The results are encouraging: The survey was able to obtain useful information from eleven-year-old census data to target high-concentration sample areas; it successfully recruited and trained bilingual staff; it enlisted respondents' cooperation at acceptable rates; and it elicited responses to sensitive questions, including immigration status, that are critical for developing and assessing policy. The authors conclude that costs for a similar survey conducted in selected sites across the country, though substantial, would be low compared with the potential costs that immigration may impose, or even with the costs of programs intended to address immigration issues. Appendixes contain the survey materials.
"Center for Research on Immigration Policy"--Cover.
Includes bibliographical references (p. 155-156).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Demographic surveys -- Research; Immigrants -- Research -- United States; United States -- Emigration and immigration -- Research